How to Boost Productivity in the EU - Klaus Weyerstrass (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Advances in total factor productivity (TFP) are important for sustaining economic growth in modern economies, in particular in the face of a declining working-age population. In this Policy Brief, we identify investment in research and development, good governance, the capital intensity, a high share of information technology in the total capital stock, and the number of industrial robots per employee as conducive for TFP growth. Based on the empirical results, policies that are beneficial for capital formation in general, investment in computer technology, research and development as well as the use of industrial robots could boost TFP in Europe.
Keywords: 330